Is the increased risk of preterm birth following excision for cervical intraepithelial neoplasia restricted to the first birth post treatment?. (9th April 2015) - Castañon, A; Landy, R; Brocklehurst, P; Evans, H; Peebles, D; Singh, N; Walker, P; Patnick, J; Sasieni, P; the PaCT Study Group
<x xml:space="preserve">Abstract</x> Objective To explore whether the increased risk of preterm birth following treatment for cervical disease is limited to the first birth following colposcopy. Design Nested case–control study. Setting Twelve NHS hospitals in England. Population All nonmultiple births from women selected as cases or controls from a cohort of women with both colposcopy and a hospital birth. Cases had a preterm (20–36 weeks of gestation) birth. Controls had a term birth (38–42 weeks) and no preterm. Methods Obstetric, colposcopy and pathology details were obtained. Main outcome measures Adjusted odds ratio of preterm birth in first and second or subsequent births following treatment for cervical disease. Results A total of 2798 births (1021 preterm) from 2001 women were included in the analysis. The risk of preterm birth increased with increasing depth of treatment among first births post treatment [trend per category increase in depth, categories <10 mm, 10–14 mm, 15–19 mm, ≥20 mm: odds ratio (OR) 1.23, 95% confidence interval (95% CI) 1.12–1.36, P < 0.001] and among second and subsequent births post treatment (trend OR 1.34, 95% CI 1.15–1.56, P < 0.001). No trend was observed among births before colposcopy (OR 0.98, 95% CI 0.83–1.16, P = 0.855). The absolute risk of a preterm birth following deep treatments (≥15 mm) was 6.5% among births before colposcopy, 18.9% among first births and 17.2% among second and subsequent births post treatment. Risk of preterm birth (once depth was accounted for) did not differ when comparing first births post colposcopy with second and subsequent births post colposcopy (adjusted OR 1.15, 95% CI 0.89–1.49). Conclusions The increased risk of preterm birth following treatment for cervical disease is not restricted to the first birth post colposcopy; it remains for second and subsequent births. These results suggest that once a woman has a deep treatment she remains at higher risk of a preterm birth throughout her reproductive life. Tweetable abstract Risk of preterm birth following large treatments for cervical disease remains for second and subsequent births.